TRPM7 channels regulate breathing during sleep in obesity by acting peripherally in the carotid bodies. (21st October 2022) - Kim, Lenise J.; Shin, Mi‐Kyung; Pho, Huy; Tang, Wan‐Yee; Hosamane, Nishitha; Anokye‐Danso, Frederick; Ahima, Rexford S.; Sham, James S. K.; Pham, Luu V.; Polotsky, Vsevolod Y.
Abstract : Abstract: Sleep‐disordered breathing (SDB) affects over 50% of obese individuals. Exaggerated hypoxic chemoreflex is a cardinal trait of SDB in obesity. We have shown that leptin acts in the carotid bodies (CB) to augment chemoreflex and that leptin activates the transient receptor potential melastatin 7 (TRPM7) channel. However, the effect of leptin‐TRPM7 signalling in CB on breathing and SDB has not been characterized in diet‐induced obesity (DIO). We hypothesized that leptin acts via TRPM7 in the CB to increase chemoreflex leading to SDB in obesity. DIO mice were implanted with EEG/EMG electrodes and transfected with Lepr b short hairpin RNA (shRNA) or Trpm7 shRNA vs . control shRNA in the CB area bilaterally. Mice underwent a full‐polysomnography and metabolic studies at baseline and after transfection. Ventilatory responses to hypoxia and hypercapnia were assessed during wakefulness. Lepr b and Trpm7 were upregulated and their promoters were demethylated in the CB of DIO mice. Lepr b knockdown in the CB did not significantly affect ventilation. Trpm 7 knockdown in the CB stimulated breathing during sleep in normoxia. These effects were not driven by changes in CB chemosensitivity or metabolism. Under sustained hypoxia, Trpm7 shRNA in the CB augmented ventilation during sleep, but decreased oxyhaemoglobin saturation. We conclude that the suppression of TRPM7 in the CB improved sleep‐related hypoventilation and that the respiratory effects of CB TRPM7 channels in obesity are independent of leptin. TRPM7 signalling in the CB could be a therapeutic target for the treatment of obesity‐related SDB. Key points: The leptin‐TRPM7 axis in the carotid bodies may play an important role in the pathogenesis of sleep‐disordered breathing. TRPM7 channels regulate breathing during sleep by acting peripherally in the carotid bodies. Suppression of TRPM7 signalling in the carotid bodies improves the obesity‐induced hypoventilation in mice. Pharmacological blockade of TRPM7 channels in the carotid bodies could be a therapy for sleep‐disordered breathing in obesity. Abstract : Abstract figure legend In diet‐induced obese (DIO) mice, a model of obesity‐induced sleep‐disordered breathing (SDB) and leptin resistance, the knockdown of long isoform of leptin receptor (LEPR b ) in the carotid bodies (CB) does not affect breathing during sleep. The knockdown of transient receptor potential melastatin 7 (TRPM7) channels in the CB stimulates breathing during sleep under normoxia ( F I O 2 F_IO_2 = 20.9%). Under hypoxia ( F I O 2 F_IO_2 = 10%), Trpm7 shRNA augments breathing, but it exacerbates oxyhaemoglobin desaturation.